Inventory Planning for XYZ Mart using EOQ and Monte Carlo - Fadhil, Muhammad; Suryani, Erma (IPTEK Journal of Proceedings Series, 2020)
XYZ Mart is a convenience store in Tulungagung regency. Founded in 2012, this store is designed to serve the daily needs of surrounding residents. In addition, this store also caters for the needs of families visiting patients at the hospital in front of XYZ Mart. Along with the store growth, there are more and more customers, and so the more demand. To handle the increasing demand, the store has to increase its inventory of goods. Problems arise when the number of goods keep increasing while the store inventory space does not. Therefore, in order to avoid overstocking or understocking, a research and planning are conducted to determine the optimal number of an order. The method used for inventory optimization is Economic Order Quantity (EOQ) to calculate the most optimal number of goods ordered. To anticipate the uncertainty of demand, Safety Stock (SS) is also used. To determine the average demand per year based on historical data, as a basis for EOQ and SS calculations, a Monte Carlo simulation is used. The expected outcome of this research is to provide recommendations of when and how much goods must be ordered so that the store can optimally use its limited space of inventory.